4 - Médias et publicisation de la sphère privée au Cameroun - Nelem, Christian Bios (Africa Development, 2021)
This article is aimed at showing that the private sphere has invaded the public sphere through the phenomenon of mediatization, to the point of questioning the conventional line drawn between what is viewed as pertaining to public life, on the one hand, and what is thought of as pertaining to private life, on the other hand. The fluctuation of this bor- derline is heightened not only by the role that the media play in this day and age in the daily lives of individuals, but also by the close ties that now exist between the political scene and the communication process. Indeed, mediatization should not be viewed merely as the exposure of large swathes of the private lives of politicians in the press or on radio, television or the Internet, but also as a modern communication strategy that aims to recreate proximity between personalities and the public. Thus, we have witnessed the development, not only of politically- oriented programmes that draw on the private sphere of political actors to present elements that will contribute to their structuring or destructuring, but also interactive programmes where individuals speak out or share their own experiences on subjects relating to health, rela- tionships, religious beliefs, etc. In this case, the aim is to abolish the physical distance between the world and the media, i.e. the world of show-business and staging, and the world as it is actually experienced. While the spectacle of reality then appears as reality itself, taking ac- count of the unique features of the Cameroonian milieu is a significant indicator that c n help identify the emergence of the private sphere in the public sphere.